Critique of Aspects of Translation of the Poetry of Pre-Islamic Poets and also of “Wormhoudt’s” Translation of al-Mutanabbi - Salim Ali, Salah (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1990)
AbstractErrors arise in the translation of poetic literature as a result of gaps in the translator's knowledge of the historical, social, and cultural context in which the poem was written. However, it is not enough for the translator to have knowledge of this sort, he must also know about the kind of idiomatic expressions in vogue which the poet tends to use and the contemporary allusions intended in his choice of words, metaphors..., etc. A further source of error stems from a misunderstanding of grammatical, or stylistic features of the poetry. All poets manipulate the grammar of their language in their own characteristic way. Unless the translator is well acquainted with these features, he may not faithfully represent their semantic effect in the target language. This paper deals with some cultural and linguistic aspects of some translations of the pre-Islamic poets and also of "Wormhoudt's" translation of al-"Mutanabbi" with examples of errors arising from cultural and linguistic misunderstanding.